2015
DOI: 10.1111/jnc.13027
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic control of mRNA stability modulates circadian amplitude of mouse Period3 mRNA

Abstract: The daily oscillations observed in most living organisms are endogenously generated with a period of 24 h, and the underlying structure of periodic oscillation is an autoregulatory transcription-translation feedback loop. The mechanisms of untranslated region (UTR)-mediated post-transcriptional regulation (e.g., mRNA degradation and internal ribosomal entry site (IRES)-mediated translation) have been suggested to finetune the expression of clock genes. Mouse Period3 (mPer3) is one of the paralogs of Period gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 66 publications
0
35
0
Order By: Relevance
“…RNA splicing, polyadenylation, and mRNA stability exhibit circadian dynamics that can exert a direct impact on gene expression control, including clock genes and downstream circadian-controlled genes (Kim et al, 2015; Koike et al, 2012). Fustin et al (2013) provided the evidence for modulation of m 6 A RNA methylation on clock gene stability, revealing that m 6 A RNA methylation regulates RNA processing including RNA export and stability, and affects clock gene dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…RNA splicing, polyadenylation, and mRNA stability exhibit circadian dynamics that can exert a direct impact on gene expression control, including clock genes and downstream circadian-controlled genes (Kim et al, 2015; Koike et al, 2012). Fustin et al (2013) provided the evidence for modulation of m 6 A RNA methylation on clock gene stability, revealing that m 6 A RNA methylation regulates RNA processing including RNA export and stability, and affects clock gene dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are modeled with mRNA expression as input and consider only constitutive translation and protein decay; however, circadian regulation has also been described to occur on the posttranscriptional and posttranslational levels (24,56,(101)(102)(103)(104)(105)(106)(107)(108)(109)(110)(111)(112). Therefore, further studies should aim to quantify degradation and production rates of mRNA and/or protein or assess protein levels in circadian rhythm, as done in several studies (109,111,112), and consequently expand and improve the modeling approach (113)(114)(115).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of both these types of DBP mRNA decreased after knockdown of hnRNP K (Figure 5A). Per3, which has been reported to retain mRNA stability through hnRNP K, was used as a positive control (20). In addition, we elucidated the kinetics of mRNA decay to exclude the possibility of mRNA degradation, which was previously reported to be related to the function of hnRNP K (20).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that clock genes are controlled by core genes such as the BMAL1-CLOCK complex, which acts as an activator (5, 6), and Cryptochrome (Cry1 and Cry2) (7, 8) along with Period (Per1, Per2, and Per3) (9-12) genes, which function as repressors. Recently, post-transcriptional regulation of clock genes by RNA-binding proteins such as hnRNP Q (13-15), PTB (16), hnRNP D (17), hnRNP A1 (18), hnRNP R (19), and hnRNP K (20) was shown to play a role in circadian rhythm.…”
Section: Introductionmentioning
confidence: 99%